The Strength of Figures and Characteristics of Political Party Leaders in the 2024 Simultaneous Regional Head Election in Indonesia - Al Syahrin, M. Najeri (Technium Social Sciences Journal, 2024)
This paper projects that the figures and characteristics of leaders are needed in the power of political parties, especially in contesting simultaneous regional elections in Indonesia. In the 2014 and 2019 elections, Jokowi and Prabowo Subianto, respectively, were two central figures in each party. Analysis of survey data for eight Indonesian elections shows that party leadership and identity are the most important determinants of party votes in legislative and presidential elections. Political parties must correctly place a central figure in their respective parties. The central figure serves as a booster, navigator, and inspiration for party cadres. In addition, figures can also be public reference material to choose one political party, when it is difficult for people to distinguish ideology between one party and another. Nevertheless, the system, traditions, and regeneration process must run as it should. Because only systems, traditions, and regeneration will be the foundation of the future. Political parties as a large organization are certainly not enough to rely on only one individual. There must be a regeneration of leadership within the party. So, if the central figure is no longer in the party, the party can still survive to maintain its existence in society.